Assessment of risk factors and transmission for HIV comparing discordant and concordant couples in Hlabisa Demographic Surveillance System (DSS) site. - Adjei, George (My University, 2010)
Objective To compare risk factors between HIV-positive concordant and discordant couples. Study design This is a cross-sectional secondary data analysis study using data from Africa Centre Demographic Information System (ACDIS) database (June 2003 to December 2004) and data from the first round of population-based HIV surveillance conducted by the Africa Centre for Health and Population Studies. Methods Eighty-five HIV-positive concordant couples (both partners were HIV-positive) and 73 discordant couples (one partner was HIV-positive and other partner HIV-negative) were identified and selected from the first round of population-based HIV surveillance conducted from June 2003 to December 2004 in Hlabisa Demographic Surveillance System site. Partners health and sexual behaviour data were collected together with the blood sample for HIV test during the same round. Socio-economic and demographic data of partners were obtained from the ACDIS database and were collected within the same period (June 2003 to December 2004). The behavioural, biological, demographic and socio-economic risk factors for HIVpositive concordance and transmission within discordant couples were analysed. Circumcision and area of residence respectively were the biological and demographic factors considered. Number of household assets was used as a proxy for socioeconomic status. The behavioural factors considered were male condom-use, sexual debut (age at first sex), number of lifetime partners and premarital partners. The age and educational level of partners were considered as potential confounders. 5 RESULTS The uncircumcised men were more likely to be in HIV-positive concordant couples than to be in discordant couples (OR =10.8, 95% CI [1.93 – 60.30], p=0.007). Partners living in urban area were 4.7 times more at risk of being in a HIV-positive concordant relationship than to be in discordant relationship (OR=4.7, 95% CI [2.09 - 10.39], p<0.001). Male not using condom on regular basis with female partners, early sexual debut, greater number of premarital partners, household assets and lifetime partners were found not to be significantly associated with HIV-positive concordance. Conclusion There are several biologic, socio-economic, demographic and behavioural risk factors for HIV-positive concordance. However, identifying some of them might be used to address transmission of HIV among discordant couples through intervention programs. Although cross-sectional studies are not ideal for establishing temporality, this study corroborates the findings of other studies that living in urban areas and circumcision are associated with HIV transmission.
MSC (Med),Population-Based Epidemiology, Faculty of Health Sciences, University of the Witwatersrand, 2007
Keywords: HIV; transmission; risk factors